Enhancement of revenue collection efficiency of Chaiyaphum Municipality - Detthamrong, Umawadee; Machaiyaphum, Junjira; Saenkhen, Sasiphon; Wannok, Supawadee (Journal of Management Science Nakhon Pathom Rajabhat University, 2024)
The purposes of this study were as follows: 1) to study factors affecting the efficiency of revenue collection of Chaiyaphum Municipality and 2) to compare factors affecting the efficiency of revenue collection of Chaiyaphum Municipality as classified by demographic characteristics. A survey research method was employed using questionnaires as a research instrument. The samples used in this study comprised of 400 persons of people who live in Chaiyaphum municipality and are the ones who have to pay land and building tax and signboard tax. Data was analyzed using descriptive and inferential statistics techniques. The research results showed that: 1) in an overall, factors affecting the efficiency of revenue collection of Chaiyaphum Municipality, were at a highest level. In details, the highest average of components of the efficiency of revenue collection of Chaiyaphum Municipality was awareness of duty of the tax payer, followed by structure, personnel, and place and equipment, respectively. 2) The results of the hypothesis testing reveal that in overall, respondents who were different age, education level, occupation and monthly income, had different levels of opinions about factors affecting the efficiency of revenue collection of Chaiyaphum municipality, statistical significant at the 0.05 level. Article history: Received 5 September 2023 Revised 20 December 2023 Accepted 28 December 2023 SIMILARITY INDEX = 1.65 %